Physical dynamics of Lake Victoria over the past 34 years (1984–2018): Is the lake dying? - Awange, Joseph; Saleem, Ashty; Sukhadiya, R.; Ouma, Y.; Kexiang, H. (Elsevier, 2019)
Understanding changes in the physical dynamics of lakes (e.g., areas and shorelines) is important to inform policies, planning and management during climate extremes (e.g., floods and droughts). For Lake Victoria, the world's second largest freshwater lake, its physical dynamics and associated changes are not well understood as evidenced, e.g., from the citations of its area 66,400 – 69,485 km2, length 300 – 412 km, width 240 – 355 km, and shorelines 3300 – 4828 km. Its sheer size and lack of research resources commitment by regional governments hamper observations. This contribution employs a suite of remotely sensed products for the past 34 years (1984–2018); Landsat, Sentinel-2, MODIS, Google Earth Pro, CHIRPS, Multivariate El’ Niño-Southern Oscillation Index and altimetry data together with the physical parameters from 37 publications (1969–2018) to (i) study the lake's dynamics and establish its current (2018) state, (ii) identify and analyse hotspots where significantly dynamic changes occur, and (iii), study the contributions of climate change and anthropogenic activities on these dynamics. Utilizing manual digitisation, MNDWI, NDVI and PCA methods, the study shows the lake's mean surface area to be 69,295 km2 (i.e., 812 km2 or 1.2% more than that of the 37 publications) and its 2018 value to be 69,216 km2 (i.e., ~733 km2 (1.1%) more than that of the 37 publications). As to whether the lake is dying, it shrunk by 203 km2 (0.3%) compared to its 1984 value, a decrease noted mainly in four hotspot Gulfs (Birinzi 40%, Winam 20%, Emin Pasha 38% and Mwanza 55%). Correspondingly, the expansion of Nalubaale Dam (2002–2006) decreased the areas by 31%, 10%, 21% and 44%, respectively. Seasonal analysis shows an increase of 9 km2 in the lake's area during the heavy rainy season (March–May) while the ENSO enlarged the area by 0.23% (2007) and 0.45% (2010). It is evident, therefore, that both climate variability/change and anthropogenic activities are exerting a toll on the tropical's largest freshwater body thereby necessitating careful exploitation and management plans.